1967
DOI: 10.1021/bi00854a017
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Latex Beads by Acanthamoeba. I. Biochemical Properties*

Abstract: ABSTKACT : Acanthamoebu sp. take up polystyrene and polyvinyltoluene latex beads. There appear to be no requirements for specific organic molecules for uptake providing the appropriate osmotic conditions are maintained. This requirement can be satisfied by glucose, mannitol, inulin, or proteose-peptone. The proper osmolarity depends on the previous history of the amoebas and they can adapt to an unfavorable osmolarity. Uptake is inhibited by 2 X M dinitrophenol, 2 x M cyanide, and 2 X M azide but not by 4 x 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(102 citation statements)
references
References 21 publications
9
93
0
Order By: Relevance
“…Cell samples taken at 15-min intervals were assayed for yeast content and bead uptake . The bead content was determined spectrophotometrically as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…Cell samples taken at 15-min intervals were assayed for yeast content and bead uptake . The bead content was determined spectrophotometrically as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…During endocytosis, the plasma membrane invaginates and encloses extracellular fluid (pinocytosis) or particles (phagocytosis) in plasma-membrane-derived vesicles. This process leads to an extensive internalization of plasma membrane varying between 1 and 20 times the total cell surface area per hr, depending on cell type and culture conditions (6)(7)(8)(9)(10)(11)(12). However, during endocytosis no reduction of the cell surface area is observed.…”
Section: Ammentioning
confidence: 99%
“…Although the lysosomal system of Acanthamoeba has not yet been studied in detail, its essential features appear to be typical of those found in other phagocytic cells. In ingesting particulate matter greater than I #m in diameter, the ameba closely surrounds each particle with its plasma membrane (12,28); the membrane-enclosed particle then buds off into the cytoplasm, giving rise to a newly formed phagosome (9,29), which is observed to fuse subsequently with other members of the vacuolar system and to acquire a variety of hydrolytic enzymes (29). In sucrose gradients of Acanthamoeba extracts, MUller (17) has shown the presence of six sedimentable acid hydrolases, each with an almost identical distribution pattern which is distinct from the mitochondrial and peroxisomal patterns.…”
Section: Ysosomal Nature Of the Vacuolesmentioning
confidence: 99%
“…The foundation for attempting this study was largely laid by the work of Weisman and Korn (28) who observed that PS and PVT beads were ingested by Acanthamoeba, and by the subsequent work of Wetzel and Korn (29) who reported observing the in vivo fusion of PS-labeled vacuoles and showed that PS vacuoles could easily be isolated on sucrose step gradients. Since PS and PVT particles differ substantially in their densities, sucrose gradient analysis of in vitro mixtures of Acanthamoeba homogenates labeled with these two particles seemed to be a promising system with which to attempt to demonstrate in vitro fusion of the vacuoles.…”
Section: Development Of the In Vitro Systemmentioning
confidence: 99%